2007
DOI: 10.1634/stemcells.2007-0640
|View full text |Cite
|
Sign up to set email alerts
|

Derivation, Characterization, and In Vitro Differentiation of Canine Embryonic Stem Cells

Abstract: Canine embryonic stem (cES) cell lines were generated to establish a large-animal preclinical model for testing the safety and efficacy of embryonic stem (ES) cell-derived tissue replacement therapy. Putative cES cell lines were initiated from canine blastocysts harvested from natural matings. Times of harvest were estimated as 12-16 days after the presumed surge in circulating levels of luteinizing hormone. Four lines established from blastocysts harvested at days 13-14 postsurge satisfied most of the criteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(65 citation statements)
references
References 36 publications
4
57
0
2
Order By: Relevance
“…CD9 belongs to the tetraspanin family and is considered as a pluripotency marker [36] . Afterwards Chaker N. Adra discovered and patented [37] that pluripotent stem cell populations could be obtained from olfactory mucosa and reported that some cells of the pluripotent stem cell population could differentiate into cells of one or more various lineages such as mesenchymal lineages or neuronal lineages or both. Thus, in this study, we also investigated the expression of pluripotent genes such as OCT4, Nanog and Sox2 because canine embryonic stem cells were demonstrated to express Oct4, Nanog, and Sox2 at high levels [38] .…”
Section: Discussionmentioning
confidence: 99%
“…CD9 belongs to the tetraspanin family and is considered as a pluripotency marker [36] . Afterwards Chaker N. Adra discovered and patented [37] that pluripotent stem cell populations could be obtained from olfactory mucosa and reported that some cells of the pluripotent stem cell population could differentiate into cells of one or more various lineages such as mesenchymal lineages or neuronal lineages or both. Thus, in this study, we also investigated the expression of pluripotent genes such as OCT4, Nanog and Sox2 because canine embryonic stem cells were demonstrated to express Oct4, Nanog, and Sox2 at high levels [38] .…”
Section: Discussionmentioning
confidence: 99%
“…Obtaining of ES cell lines from species other than mouse and man has proved even more difficult. Protocols optimised for derivation and culture of mouse ES cells were not suitable for establishment of embryonic stem cells from hamster (Doetschman et al, 1988); mink (Sukoyan et al, 1992); dog (Hatoya et al, 2006;Hayes et al, 2008); cat (Yu et al, 2008); rabbit (Honda et al, 2008); horse (Saito et al, 2002); pig (Notarianni et al, 1990;Notarianni et al, 1991;Wheeler, 1994;Li et al, 2003); sheep (Notarianni et al, 1991); buffalo (Verma et al, 2007) and until recently from rat (Iannaccone et al, 1994;Vassilieva et al, 2000;Schulze et al, 2006;Demers et al, 2007). Bank vole seems to be yet another species supplementing the list of ES cells derivation trials.…”
Section: Discussionmentioning
confidence: 99%
“…However, the used technology still needs optimization as they undergo spontaneous differentiation over long-term culture, irrespective of the source of derivation, that is, in vivo or in vitro produced blastocysts. Canine ESCs have also been isolated from pre-implantation stage embryos with both in vitro and in vivo differentiation potential (Hatoya et al 2006;Hayes et al 2008;Schneider et al 2008;Vaags et al 2009;Wilcox et al 2009;Schneider et al 2010). These canine ESCs were able to undergo self-renewal for prolonged periods of culture while remaining undifferentiated, and expressed a characteristic pluripotency gene expression profile, such as OCT4, SSEA3 and SOX2.…”
Section: Embryonic Stem Cells In Domestic Animalsmentioning
confidence: 99%